Outbreak of enteric fever: a fact finding mission - Pardal, Maninder Pal Singh; Minhas, Sukhmeet (International Journal Of Community Medicine And Public Health, 2020)
Background: In September 2019, a large number of fever cases among troops and families in a military station in Maharashtra were admitted to the local Military Hospital. Detailed epidemiological investigations revealed the cause to be an outbreak of enteric fever due to sewage contamination of drinking water. Methods: A detailed site survey was undertaken; and a descriptive epidemiological study was carried out. Routine haemogram, blood culture, antibiotic sensitivity test besides serotyping of the isolates were carried out. Results: In all 28 cases who fulfilled the case definition criteria were admitted in the month of September 2019. Out of these 21 (75%) were confirmed by blood culture, while the remaining were probable cases. Bacteriological examination reports of water samples taken from various source as well as consumer end points both prior to beginning of the outbreak and during the outbreak revealed a high presumptive coliform count. Spatial and temporal clustering of cases was suggestive of common source outbreak. On 16 September 2019 exploration by digging was carried out undertaken which revealed massive leakage of water in close proximity to the overflowing manholes. The outbreak was promptly controlled after detection of this pipeline and provision of alternative source of water supply to the affected area. Conclusions: Salmonella enterica serovar typhi has been implicated in many outbreaks through history. The present outbreak was a common source focal outbreak due to sewage contamination of drinking water in a few areas in the station.